An MR-Compatible Stage for Respiratory Motion Emulation. Issue 1 (July 2017) - Simonelli, James; Lee, Yu-Hsiu; Mikaiel, Samantha; Chen, Cheng-Wei; Li, Xinzhou; Sung, Kyung; Lu, David; Wu, Holden; Tsao, Tsu-Chin
Abstract: We present the development of a system that physically emulates respiratory motion for phantoms under Magnetic Resonance Imaging (MRI). The system is designed to be inherently MR-compatible—with no ferrous materials or electromagnetic actuators present in the exam room—and uses hydrostatic actuators to control motion of the phantom. MR-compatibility of the system is verified through both signal-to-noise ratio (SNR) and imaging distortion tests, and several control strategies are then implemented to achieve tracking of prerecorded respiratory motion profiles obtained from a human subject.